Multicenter randomized crossover trial evaluating the provox luna in laryngectomized subjects. (20th February 2019) - Ratnayake, Chathura B.B.; Fles, Renske; Tan, I. Bing; Baijens, Laura W.J.; Pilz, Walmari; Meeuwis, Cees A.; Janssen‐van Det, Pauline H.E.; van Son, Rob; Van den Brekel, Michiel W.M.
Abstract : Objectives: The aim of this study was to compare the relative compliance and the dermatological and pulmonary outcomes when the Provox Luna system (Atos Medical, Malmö, Sweden) is added during the night to the usual tracheastoma care of laryngectomized subjects. Methods: This was a multicenter randomized crossover trial conducted in the Netherlands Cancer Institute, Erasmus Medical Center, and Maastricht University Medical Center in The Netherlands. The study included 46 laryngectomized subjects with prior heat and moisture exchanger (HME) and adhesive experience. Results: A significant improvement in the number of compliant individuals was found: Luna: n = 43 of 45 (96%); usual care: n = 35 of 46 (76%), P = 0.02. The Luna period was associated with longer intervals of daily HME use (Luna 23.2 hours [range: 15.6–24.0 hours], usual care [UC]: 21.5 hours [range: 6.0–24.0 hours], P = 0.003) and an increased frequency of skin improvement overnight (Luna 3.9 days [standard deviation (SD)]: 7.0 days), Usual Care: 8.1 days ([SD: 10.8 days], P = 0.008). Fifty‐six percent (n = 26) of participants wanted to continue using the Provox Luna system at the conclusion of the study. Conclusion: An improvement in compliance and skin recovery overnight was observed when the Provox Luna was added to the usual adhesive and HME use. Therefore, there is utility in supplementing the usual post‐total laryngectomy care with the Provox Luna system at night, particularly in the setting of compliance concerns and in subjects who desire dermatological relief overnight. Level of Evidence: 1b Laryngoscope, 129:2354–2360, 2019